Analysis of Human Development Index in West Nusa Tenggara Province with Spatial Panel Model - Alfira Mulya Astuti; Afifurrahman Afifurrahman; Habibi Ratu Perwira Negara ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2024)
The purpose of this article is to examine the factors that influence the human development index (HDI) in West Nusa Tenggara using a spatial panel model. This research is crucial because it can analyze correlations between regions and is more efficient, informative, and effective in HDI modeling. The data structure is panel data, where observation units are the cities and regencies in West Nusa Tenggara Province for 2010 to 2022. A human development index serves as the dependent variable. The independent variables were per capita expenditure, average length of school, length of school expectations, and life expectancy. The Rook contiguity and the customized matrix (transportation routes) are used to examine geographical impacts. The results of the analysis indicate: 1) there are spatial linkages between districts and cities in West Nusa Tenggara; 2) the SAR Fixed Effect model is the most appropriate spatial model to model the human development index; 3) the human development index can be improved simultaneously by factors such as life expectancy, expected length of schooling, average length of schooling, and per capita expenditure; and 4) life expectancy is the main factor affecting the human development index.